Analisis Pengurangan Defect pada Produksi Wide Flange (H-Beam) dengan Metode DMAIC - Erika Erika; Nataya Charoonsri Rizani (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract With changes in technology and the increasing internationalization of manufacturing, production has become the main approach for benefiting from globalization and being able to bridge income gaps with the industrial world. In making Wide Flange (H-beam) at PT. X found several product defects such as dimensions not according to shop drawings, holes not centered during assembly, number of holes not according to drawings, undercuts, and porosity. To improve the quality of the Wide Flange (H-Beam) product at PT X, it is necessary to take corrective steps for product defects that occur. One of the continuous quality improvement programs to overcome product defects that occur with the DMAIC stages. Based on the research results, it can be concluded that the sigma level and DPMO value of the company is 50.331 with a possible damage of 47,893 pieces. After analyzing using a Pareto diagram, it was found that the type of defect, the number of holes that do not match the drawing with a percentage of 29% and holes not centered during assembly with a percentage of 32%, is the most common. And based on the results of the FMEA analysis, one of the causes of defects in the hole not being a flashlight during assembly is improper installation with an RPN value of 144 and the cause of the defect in the number of holes not conforming to the drawing is not following the drawing with an RPN value of 140. Keyword : DMAIC, DPMO, FMEA, RPN, Wide Flange (H-Beam)